PEMBERIAN AMELIORAN DAN ISOLAT BAKTERI FIKSASI NITROGEN NON SIMBIOTIK (FNNS) UNTUK MENINGKATKAN PERTUMBUHAN DAN SERAPAN N TANAMAN PADI GOGO (Oryza sativa L.) PADA MEDIUM ULTISOL - Yoggie Prathama; Nelvia Nelvia; Al Ikhsan Amri (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2018)
The need of rice as the staple food of the people of Indonesia has a deficit every year. Upland rice cultivation in dry land such as Ultisols became one of the alternatives to meeting the needs of rice. However, productivity of crop in Ultisols is low because of some problems of acidity and nutrients deficiency. It is necessary input such as ameliorants like biochar cocopeat of oil palm empty bunch compost (OPEBC) and the use of bacterial non-symbiotic nitrogen fixation (NSNF) to fix the problems. The research aims to study the effect of application of ameliorant and suspensions of bacterial isolates of NSNF on growth and N uptake by upland rice in Ultisols medium. The research was conducted at the Green House of the Faculty of Agriculture, University of Riau, Pekanbaru from Mei to September 2017. The research in form factorial experiment was arranged a completely randomized design (CRD). The first factor were ameliorant, consists of six type (biochar, cocopeat, OPEBC, biochar+cocopeat, biochar+OPEBC, each doses 50 g polybag-1 and without ameliorant as a control). The second factor were suspensions of bacterial isolates of NSNF, consists of three levels (10 and 20 ml polybag-1 and without bacterial isolates as a control). The parameters observed were plant height, number of tillers, weight of dry shoot and roots, N uptake by shoot and roots. The results show that the application of ameliorant (biochar, cocopeat, OPEBC, biochar + cocopeat, biochar + OPEBC), each doses of 50 g polybag-1 and suspensions of bacterial isolates of NSNF doses of 0, 10 and 20 ml polybag-1 increased plant height, number of tillers, weight of dry shoot and N uptake by shoot compared to control and the application of without ameliorant with suspension of bacterial isolates of NSNF doses of 0, 10 and 20 ml polybag-1.Key words : biochar, cocopeat, palm oil empty bunch, upland rice, ultisol